Development Times and Approval Success Rates for Drugs to Treat Infectious Diseases. Issue 2 (11th October 2019) - DiMasi, Joseph A.; Florez, Maria I.; Stergiopoulos, Stella; Peña, Yaritza; Smith, Zachary; Wilkinson, Michael; Getz, Kenneth A.
Abstract : We gathered data from three pipeline databases and other public sources on development stage and clinical trial metrics for 1, 914 investigational drugs, biologics, and vaccines and 2, 769 clinical trials intended to treat a wide variety of infectious diseases. We included new molecular entities (NMEs), new formulations, and new combinations. Clinical trial times decreased from 2000–2008 to 2009–2017, varied by disease class, and were longer for trials with more subjects or more sites. Clinical approval success rates were higher for this set of diseases than those in the published literature for drugs across all therapeutic categories. NMEs to treat HIV had a success rate (16.0%) that was similar to those for drugs in general, whereas NME success rates for influenza and pneumonia were much higher (48.1% and 50.5%, respectively).